Review of the book by Gerhard Werle, Principles of International Criminal Law (The Hague, The Netherlands: TMC Asser Press, 2005), 488 pp. - S. V. Sayapin (Московский журнал международного права, 2008)
The review appraises a recent treatise on international criminal law written by Dr. Gerhard Werle, Professor of German and international criminal law at the Alexander-von-Humboldt University in Berlin. Unlike some earlier treatises on international criminal law, which had contained a combined presentation of both international criminal law and procedure, G. Werle’s work focuses exclusively on material law. The book is subdivided in six parts and expounds in a detailed way the foundations, principles and systembuilding institutions of international criminal law, as well as comments profoundly the elements of core international crimes – genocide, crimes against humanity, war crimes and aggression.Summing up the main approaches towards elements of crimes in international criminal law, the author concludes that, unlike in domestic criminal law systems, international crimes have three elements under international criminal law: material element, psychological element, as well as the existence or absence of circumstances which exclude criminal responsibility. This theoretical construction brings to an “average” common denominator the Anglo-Saxon concept which encompasses only two elements of crimes (so-called actus reus and mens rea), and the continental one, which “splits” crimes into four elements (subject and subjective aspect of a crime, object and objective aspect of a crime). The specific elements of international crimes, which are considered in subsequent Parts, are further characterised from the point of view of those three elements It is suggested that the book, due to its superb academic quality and scholarly value, would be of a definite use to international lawyers.